The Role of Transportation Costs on Affordable Housing for Low-Income Class - Khabiri, Mohammad Mehdi; Pour Ghasem Abadi, Saeed Nemati; Fard, Zohreh Ghafori (Communications - Scientific Letters of the University of Zilina, 2023)
This research was conducted to investigate the current state of transportation, as well as the transportation costs of the residents of towns with affordable residential houses, by preparing and presenting a questionnaire to these residents. In this questionnaire, things like housing costs, the amount of travel to the city center, satisfaction with public transportation services and its variety, easy access to public transportation and required places, the amount of use of public transportation and private vehicles were examined and solutions to reduce transportation costs were presented. Although the price of housing in the towns is lower than in the city center; the costs of transporting the residents of these towns are significant. In addition, the state of public transportation and access to needed places is unfavorable, so that about 60 % of the interviewees were dissatisfied with public transportation services.
Keywords: AM; affordable housing; low-income; public transportation; transportation costs; transportation of settlers